Gender Constructions and Stereotypes of Women in "Bebas" (Roland Barthes Semiotics Analysis) (Cinematology: Journal Anthology of Film and Television Studies, 2024)
'Bebas' is an adaptation of the 2019 South Korean film, directed by Riri Riza and produced by Miles Film. This comedy-drama genre film tells how gender construction and stereotypes of women are born in society. In this study, researchers used qualitative descriptive research methods with Roland Barthes semiotic analysis, used to analyze scenes that show gender constructions and female stereotypes reinforced with several references or references from books and journal articles. This study identified the meaning of denotations, connotations, and myths contained in 'Bebas' so that a result was found, namely the construction of gender and stereotype women in 'Bebas' shown in the characters of the characters Vina, Mia, and Kris.